Atomic force microscopy study of the biofouling and mechanical properties of virgin and industrially fouled reverse osmosis membranes - Lydia Powell (Desalination, 2017)
The mechanical properties of virgin and industrially fouled reverse osmosis membranes (composite polyamide) used for the purification and desalination of seawater in desalination processes were characterised using novel atomic force microscopy (AFM) methods. Polymeric surface elasticity has previously been demonstrated to strongly affect the adhesion of bacteria; hence the study examined membrane surface elasticity to demonstrate how AFM can be used to assess the bio-fouling potential of membranes. An AFM colloid probe technique was used to determine the mechanical properties of the membrane, the adhesion forces and the work of adhesion at the membrane surfaces. The mean values of Young's modulus for the virgin membrane decreased in magnitude with increasing pH values, where these values were significantly different (p < 0.017) between both pH 3 (1450 kPa), pH 7 (1327 kPa) and pH 9 (788 kPa). These differences were attributed to differences in membrane swelling and indicate possible control parameters that could be exploited to improve membrane cleaning regimes. A membrane with a higher modulus will be stronger and potentially more resistant to chemical and physical processes during operation and cleaning. Significant differences (p < 0.017) in force measurements were also found between different electrolytic conditions for each of the membranes, where for the virgin membrane the adhesion force values were 6.00 nN at pH 3, 1.77 nN at pH 7 and 0.98 N at pH 9, and also the work of adhesion were 153.6 nJ at pH 3, 22.8nJ at pH 7 and 9.9 nJ at pH 9 in 0.6 M NaCl. These observations further confirm the importance of the electrolytic environment on the nanoscale interactions of the membrane which should be considered to control fouling during operation and cleaning cycles. AFM images and streaming potential measurements of virgin and fouled membranes were also obtained to aid analysis of the industrial membrane system. The novel application of AFM to membranes to measure Young's moduli and work of adhesion is a new addition to the AFM tools that can be used to unravel separation processes at the membrane surface. In addition, this study further demonstrates that AFM force spectroscopy can be used as part of a sophisticated membrane autopsy procedure for the elucidation of the mechanisms involved in membrane fouling.